Graft-versus-Leukemia Effect Following Hematopoietic Stem Cell Transplantation for Leukemia - Dickinson, Anne M.; Norden, Jean; Li, Shuang; Hromadnikova, Ilona; Schmid, Christoph; Schmetzer, Helga; Jochem-Kolb, Hans (Frontiers in Immunology, 2017)
The success of hematopoietic stem cell transplantation (HSCT) lies with the ability of the engrafting immune system to remove residual leukemia cells via a graft-versus-leukemia effect (GvL), caused either spontaneously post-HSCT or via donor lymphocyte infusion. GvL effects can also be initiated by allogenic mismatched natural killer cells, antigen-specific T cells, and activated dendritic cells of leukemic origin. The history and further application of this GvL effect and the main mechanisms will be discussed and reviewed in this chapter.